2008
DOI: 10.1590/s1413-86702008000300001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of virologic failure after an initially successful 48-week course of antiretroviral therapy in HIV/AIDS outpatients treated in Santos, Brazil

Abstract: We characterized the virologic failure after an initially successful 48-week course of antiretroviral therapy among HIV/AIDS patients in a retrospective cohort study involving patients from Santos, Brazil. Patients with plasma HIV RNA below 500 copies/mL for 48 weeks were included. Variables analyzed included gender, age, level of education, marital status, mode of HIV acquisition, viral load, and CD4 cell count upon admission. There were 4,909 patients registered with the clinic, of which 669 patients met all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
3

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 22 publications
1
16
0
3
Order By: Relevance
“…However, these are better data than those of PINTO NETO et al 29 in 1998 and 1999 in Vitoria (ES), and CASEIRO et al 3 between 1997 and 2003 in Santos (SP) who found 50.0% and 44.0% respectively. The percentages found in the present study are also higher than those registered in the systematic review of BARTLETT et al 1 in the United States of America in 2001, in which the schemes containing PI produced an undetectable viral load in 46.0% of cases versus 51% under NNRTI.…”
mentioning
confidence: 59%
See 4 more Smart Citations
“…However, these are better data than those of PINTO NETO et al 29 in 1998 and 1999 in Vitoria (ES), and CASEIRO et al 3 between 1997 and 2003 in Santos (SP) who found 50.0% and 44.0% respectively. The percentages found in the present study are also higher than those registered in the systematic review of BARTLETT et al 1 in the United States of America in 2001, in which the schemes containing PI produced an undetectable viral load in 46.0% of cases versus 51% under NNRTI.…”
mentioning
confidence: 59%
“…The medians in G1 and G2 were 723 cells/mm 3 Tables or Figures). The analysis of plasma VL determinations is also shown in these Figures.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations